CHOREOGRAPHIC AMATEURS IN THE STRUCTURE OF NON-FORMAL ART EDUCATION: HISTORICAL AND PEDAGOGICAL DISCOURSE - Blahova, Tetiana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Development dynamics of choreographic amateur as a phenomenon of creative activity in the structure of non-formal art education is investigated in the article. The main stages of becoming a choreographic amateur in Ukraine in the context of socio-political and cultural-artistic determinants are characterized. It has been found that during the XX century choreographic activity as a component of non-formal art education had passed a difficult and contradictory path from the experiments of dance studios and the search for “Soviet dance” to the creation of groups, ensembles, creative associations, and later the appearance of amateur dancers of various genres of choreographic performances. Choreographic performance was actively implemented in the permanent and temporary forms of organization that brought together different social groups. The study analyzes the content of choreographic training in the activities of dance groups in different cultural and educational locations at different stages of historical development. The actual perspective of the development of theoretical studies in the field of choreographic education is the understanding of pedagogical resources of amateur choreography, the analysis of its strategies, meaningful content in various forms of organization.